2016
DOI: 10.4103/0972-5229.188198
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of traumatic cardiac arrest in patients presenting to emergency department at a level 1 trauma center

Abstract: Introduction:There is a paucity of literature on prehospital care and epidemiology of traumatic cardiac arrest (TCA) in India. This study highlights the profile and characteristics of TCA.Methods:A retrospective cohort study was conducted to study epidemiological profile of TCA patients ≥1 year presenting to a level 1 trauma center of India.Results:One thousand sixty-one patients were recruited in the study. The median age (interquartile range) was 32 (23–45) years (male:female ratio of 5.9:1). Asystole (253),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…[ 6 , 21 24 ] Approximately 60% of OHCA patients suffering from trauma were under 65 years old, and males accounted for approximately 60% to 80% of cases. [ 25 27 ] Most previous studies also noted that demographic indicators, such as age and gender, were associated with survival. However, our investigation detected no significant differences in survival outcome with those variables, similar to the findings of a Canadian study.…”
Section: Discussionmentioning
confidence: 99%
“…[ 6 , 21 24 ] Approximately 60% of OHCA patients suffering from trauma were under 65 years old, and males accounted for approximately 60% to 80% of cases. [ 25 27 ] Most previous studies also noted that demographic indicators, such as age and gender, were associated with survival. However, our investigation detected no significant differences in survival outcome with those variables, similar to the findings of a Canadian study.…”
Section: Discussionmentioning
confidence: 99%
“…A previous single-centered study in India reported 1061 cases of traumatic cardiac arrest arriving at the emergency department, of which only three survived to hospital discharge. [ 2 ]…”
Section: Introductionmentioning
confidence: 99%
“… 6 An epidemiological study conducted in India showed that patients presented with TRCA, either out-of-hospital cardiac arrest (OHCA) or in emergency department (ED), who were provided cardiopulmonary resuscitation (CPR), return of spontaneous circulation (ROSC) was present in 7.4% and 92.60% of the patients could not be revived. 7 …”
Section: Introductionmentioning
confidence: 99%